Role of maternal nutrition and oxidative stress in placental telomere attrition in women with preeclampsia - Aditi A. Godhamgaonkar; Deepali P. Sundrani; Sadhana R. Joshi (Taylor & Francis Group, 2021)
Background:Maternal nutrition influences the growth and development of the fetus and influences pregnancy outcome. We have earlier demonstrated altered maternal nutrition and increased oxidative stress in women with preeclampsia. Oxidative stress is known to be associated with reduced telomere length and short telomere aggregates. Increased telomere attrition leads to increased cellular senescence and tissue ageing. Methods:The present review focuses on the role of maternal nutrition and oxidative stress in telomere attrition in preeclampsia. Results and Conclusion:Future studies need to examine the association between maternal nutritional status in early pregnancy, oxidative stress and telomere attrition in preeclampsia.